Post-structural Feminism to Fight Kyriarchy: A Case of Black Widow (2021) - Saptiadi, Nur Alifia Putri; Trisnawati, Ririn Kurnia; Agustina, Mia Fitria (Language Circle: Journal of Language and Literature, 2022)
Black Widow is a sci-fi superhero movie directed by Cate Shortland. This movie narrates the lives of the black widows under the control of a secret crime organization called the Red Room Academy. In Black Widow, Natasha Romanoff as the main character and ex-black widow is shown taking down the Red Room Academy and its male leader, Dreykov. This current study utilizes a poststructural feminism approach and the concept of kyriarchy in literature to reveal the poststructural feminism inclination and the portrayal of kyriarchy in the movie. This study uses poststructural feminism and Susan Fiorenza's concept of kyriarchy as the theories. In analyzing the data, this currrent study uses visual narrative approach. The analysis reveals the postructural feminisim inclinations portrayed by Natasha Romanoff in two categories, those are infiltration and act of self-sacrifice. Moreover, the portrayal of kyriarchy is revealed through the Red Room Academy's system and Dreykov's sexist belief. This explains how sexist belief and the practice of kyriarchy by Dreykov affects the women as the target of oppression. Thus, no matter what the situation is, women are always at a disadvantage.